1974
DOI: 10.1097/00006254-197405000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Inhibition of the Prolactin Response to Thyrotropin—releasing Hormone

Abstract: influence of serum triiodothvronine (T3) and thyroxine (T4) concentrations on the release of prolactin in man was studied by determining the prolactin response to synthetic thyrotropin-releasing hormone (TRH) in hypothyroid and hyperthyroid patients before and after correction of their serum thyroid hormone abnormalities. The maximum increment in serum prolactin above the basal level (maximum A prolactin) was used as the index of response to TRH. In 12 patients with primary hypothyroidism, the maximum A prolac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
1
2

Year Published

1981
1981
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 5 publications
2
32
1
2
Order By: Relevance
“…testosterone level. An altered secretion of PRL, despite a normal basal level, might be responsible for clinical symptoms such as impotence and oligozoospermia, and for testosterone modification that can be demonstrated by an abnormal PRL response to TRH [203]. Even after careful examination, however, the differential diagnosis is complicated by the fact that some cases classified as functional because of a normal pituitary fossa at neuroradiological studies may have a micro-adenoma that escapes diagnosis.…”
Section: Radiologic Investigation Of Sellamentioning
confidence: 99%
“…testosterone level. An altered secretion of PRL, despite a normal basal level, might be responsible for clinical symptoms such as impotence and oligozoospermia, and for testosterone modification that can be demonstrated by an abnormal PRL response to TRH [203]. Even after careful examination, however, the differential diagnosis is complicated by the fact that some cases classified as functional because of a normal pituitary fossa at neuroradiological studies may have a micro-adenoma that escapes diagnosis.…”
Section: Radiologic Investigation Of Sellamentioning
confidence: 99%
“…Since the concentration of homovanilic acid is decreased in the cerebrospinal fluid in hyperthyroidism (17), the pro duction and turnover of dopamine by negative feedback may be decreased. Some investigators (18)(19) reported a diminished prolactin response to TRH in hyperthyroid ism, suggesting enhanced central dopaminergic tone.…”
Section: Introductionmentioning
confidence: 99%
“…The major mechanism causing hyperprolactinemia in primary hypothyroidism is an increase in the levels of TRH, which stimulates PRL secretion (9).…”
Section: Introductionmentioning
confidence: 99%